PENGELOLAAN SAMPAH DI TEMPAT PEMBUANGAN AKHIR (TPA) PATOMMO SIDRAP (Tinjauan Yuridis Peraturan Daerah No. 7 Tahun 2016 Tentang Pengelolaan Persampahan) - Muthmainnah; Adris (Madani Legal Review, 2020)
The development of rapid development in Sidrap district has not been matched by serious awareness of environmental impacts. Especially rubbish It is usually present as a risk for a city that moves into a big city. A large population with high growth rates results in increased volume of waste. In addition, the consumption pattern of the community contributes to creating increasingly diverse types of waste, including packaging waste that is dangerous and / or difficult to decompose by natural processes and can damage the surrounding environment. Management and handling of waste is absolutely necessary, with special attention because it involves a very vital environment. Many cities in Indonesia in developing Final Disposal Sites (TPAs) do not pay attention to the standards for making landfill and pay attention to Environmental Impact Assessment (EIA). Inevitably, many cases in big cities arise due to garbage, both household and industrial waste because they are not properly processed and managed. The waste produced by the residents of Sidrap was dumped at Patommo Kep concern's Final Disposal Site (TPA), which is currently being raised by many residents living in the area around the TPA. A pungent odor occurs during the day and night or when the garbage is flattened. Environmental pollution caused by garbage lately is growing rapidly. We have realized that the problem of waste is very disturbing to the health and balance of the environment. To handle it, it needs the active role of the community and the government, especially the respective regional governments. Based on this, this study seeks to examine whether waste management in Patommo landfill meets the applicable regulations in Perda No.7 of 2016